Pelatihan Penyusunan Laporan Keuangan Perusahaan Perdagangan Dan Manufaktur Dalam Rangka Peningkatan Kapasitas UMKM Di DKI Jakarta - Abdul Muslim (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2021)
Based on a report from the Ministry of Communication and Information, the number of MSME business actors in Indonesia in 2015 has reached + 59 million people and contributes to Gross Domestic Product (GDP) of 55%, it is expected that in 2019 the number will reach more than 60 million people. This very large number certainly requires special attention from the Government towards MSME business actors. One of the problems that are often experienced by MSMEs in Indonesia is that MSMEs do not keep books of business transactions properly. Financial reports are needed by business actors to determine the benefits obtained, to find out the total assets owned, it is necessary to submit additional capital to creditors. The use of an excel-based general ledger (GL) accounting program will make it easier for MSME entrepreneurs to compile these financial reports.